(untitled) (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Background: Obesity can be intergreted as an excessive accumulation of body fat which leads to health problems, including migraine. Obesity is associated with the metabolic syndrome, a pro-inflammatory, pro-thrombotic state that may contribute to headache development and progression. Stimulation of trigeminal nociceptor induced the release of pro inflammation substances especially calsitonin-gene related peptide (CGRP) and P substance. Those substances are found higher in migraine and obesity person. Neurogenic inflammation state was known has a big role on migraine pain. To evaluate the relationship between waist circumference with frequencies and pain intensity in Malaysian students with migraine at the University of Sumatera Utara. Method: Observational analytic with cross sectional approach. A sample of 94 people was taken based on the total sampling technique. The data obtained are presented in tabular form and then analyzed using the Chi-square Test. Result: Data were analyzed using univariate and bivariate with the Chi-square test. From 77 subjects of the study consisting of 11 people with migraine aura and 66 people with migraine without aura. Most of the study samples were female (77.9%) and an average age of 20.97 years. The majority of race obtained was Malay (50.6%), BMI whose majority was normal (58.4%). From a 11 people with migraine aura, 7 of them had normal waist circumference and of 66 people with migraine without aura 40 of them had normal waist circumference. From Univariate and Bivariate analysis showed no significant relationship between waist circumference with the frequency of migraine attacks (p = 0.489) and there was no significant relationship between waist circumference and the intensity of migraine pain (p = 0.245). Conclusion: There is no significant relationship between waist circumference with the frequency of attacks and pain intensity in Malaysian students who experience migraine.